Prediksi Tingkat Stunting Anak di Kabupaten Langkat Menggunakan Metode Regresi Linear Berganda : (Studi Kasus : Dinas PPKB-PPA Kab.Langkat) - Dhea Alfiya Ningsih; Relita Buaton; Anton Sihombing (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Stunting is a growth and development disorder in children caused by chronic malnutrition over a long period of time, especially in the first 1,000 days of life, namely from pregnancy to the first 2 years of life. There are more than 149 million (22%) toddlers worldwide who are stunted, of which 6.3 million are Indonesian toddlers. Based on data from the Ministry of Health, the stunting rate in Indonesia in 2023 was recorded at 21.5 percent, only down 0.1 percent from the previous year which amounted to 21.6 percent. Predicting the number of stunted toddlers is very important and necessary to know the stunting rate in Langkat Regency in 2024, and the prediction results can help health workers in handling and preventing the spread of stunting. The method applied to this prediction system is Multiple Linear Regression where this analysis determines whether each independent variable is positively or negatively related, the direction of the relationship between variables, and estimates the value of the dependent variable will increase or decrease. The prediction system is carried out using the RapidMiner application because this application is very appropriate to produce information output in the form of prediction results for the coming year. The prediction results obtained are an increase and decrease in 2024 in each sub-district and there are sub-districts that do not experience an increase and decrease. The sub-district with the highest number was Secanggang with approximately 177 people, and the sub-district with the lowest number of stunted children was West Berandan with approximately 55 people. Then Stabat sub-district became the sub-district that experienced the most increase in the number of stunting, which was around 15 people, and the sub-district that experienced the most decrease was Kuala sub-district with a total of approximately 23 people. From the overall results it can be calculated that the number of stunting in all districts in Langkat Regency amounted to approximately 2453 people in 2024. And testing the error rate of prediction results using RMSE in the RapidMiner application of 7.63%, where the level of accuracy in the prediction of child stunting in Langkat Regency is 92.46%.